CYBERCULTURE FRAMES CONTEMPORAR DA'WAH IN MODERN SOCIETY - Fuadi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2023)
The phenomenon of modern society has now taken root in the joints of life which has a broad impact in all fields. Internet treats in information technology have transformed into a virtual space called cyberculture, which is a society that lives in a virtual culture in interactions between individuals, groups and communities carried out through forums, newsgroups, and chats. Cyberculture is any culture that has or is emerging from the use of computer networks for communication, entertainment, and business into virtual spaces, such as: virtual self, virtual community, virtual politics, virtual economics, virtual lives, virtual sex, virtual social, virtual/cybercrime. Modern Islamic movements are now divided into four patterns of thought, namely: liberalist thought patterns, nationalist thought patterns, apologetic thought patterns, and dynamic thought patterns. With this reality, the packaging of da'wah delivery must be based on the needs of the community and rooted in Islamic aqidah according to the Al-Quran Hadith.